Automotive component innovation development and diffusion of engine management technologies - Amey, R. G. (Technovation)
Engine management systems (EMS) were studied within three automotive manufacturers with regard to US economy and emissions regulations and consumer demands in the 1970s and 1980s. Case studies of racing and sports car fuel delivery systems are discussed and it is suggested that a new, not extended, product life cycle begins.